2014
DOI: 10.1016/j.vaccine.2014.03.093
|View full text |Cite
|
Sign up to set email alerts
|

An intact signal peptide on dengue virus E protein enhances immunogenicity for CD8+ T cells and antibody when expressed from modified vaccinia Ankara

Abstract: Dengue is a global public health concern and this is aggravated by a lack of vaccines or antiviral therapies. Despite the well-known role of CD8(+) T cells in the immunopathogenesis of Dengue virus (DENV), only recent studies have highlighted the importance of this arm of the immune response in protection against the disease. Thus, the majority of DENV vaccine candidates are designed to achieve protective titers of neutralizing antibodies, with less regard for cellular responses. Here, we used a mouse model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…This also includes modulation of the host immune response, as in the case of Human Cytomegalovirus (HCMV), where the signal peptide (through regulation of cell surface expression of two NK cell ligands) differentially affected two distinct NK cell evasion pathways [38]. A recent publication [39], reported that an intact signal peptide on dengue virus E protein (ER-targeted E protein) enhanced the immunogenicity for CD8 + T cells and generated superior antibody responses when expressed from the immunogenic recombinant vaccine vector Vaccinia Ankara.…”
Section: Discussionmentioning
confidence: 99%
“…This also includes modulation of the host immune response, as in the case of Human Cytomegalovirus (HCMV), where the signal peptide (through regulation of cell surface expression of two NK cell ligands) differentially affected two distinct NK cell evasion pathways [38]. A recent publication [39], reported that an intact signal peptide on dengue virus E protein (ER-targeted E protein) enhanced the immunogenicity for CD8 + T cells and generated superior antibody responses when expressed from the immunogenic recombinant vaccine vector Vaccinia Ankara.…”
Section: Discussionmentioning
confidence: 99%
“…HBs clinical [321] 30 CTL and 16 HTL epitopes preclinical [322] Hepatitis C NS3, NS4 and NS5B (genotype 1b) preclinical and clinical [323,324] E1 and E2 (genotype 1b) preclinical [325] C, E1 and E2, p7, NS2, NS3, NS4A, NS4B, NS5A and NS5B (genotype 1a) preclinical [326] Chikungunya C, E3, E2, 6K and E1 preclinical [327] E3 and E2 preclinical [328] E3-E2, 6K-E1 or E3-E2-6K-E1 preclinical [329] Dengue Envelope (Dengue type 2 virus) preclinical [330] Envelope (Dengue type 3 virus) preclinical [331] Ebola GP (Zaire and Sudan strains) preclinical [332] CCHF GP preclinical [333] SARS Spike protein preclinical [334][335][336][337] Spike or nucleocapsid proteins preclinical [338] Nucleocapsid preclinical [339] MERS Spike protein preclinical [340] RSV F or G glycoprotein preclinical [342][343][344] Rift valley fever Gn/Gc GP preclinical [345,346] Rabies Glycoprotein preclinical [347] JEV Membrane (prM) and envelope (E) proteins (Korean strain) preclinical [348][349][350] B cell, CTL and Th multiple linear epitopes (SA14 strain) preclinical [351] Measles HA preclinical [352] F and HA preclinical [94,353] CMV Soluble GP B (gB) preclinical [354] UL55 (surface glycoprotein), UL83 (tegument protein) and UL123/e4 (nuclear protein) preclinical [355] pp65 (tegument protein) and CMV immediate early gene IE1 preclinical [356] pp65-2, gB and IE1 (Rhesus CMV) preclinical…”
Section: Modified Vaccinia Virus Ankara (Mva)mentioning
confidence: 99%
“…Barring Ser7, all residues are completely conserved in ZIKV/DENV1-4 ( Figure 2 ). A N-terminal peptide (DENV3,4-12 VGVGNRDFV) that enhances immunogenicity for CD8+ T cells when expressed from modified vaccinia Ankara includes Phe11, Ser7 and Arg9 39 . Arg9 and Glu13 are also epitopes of other antibodies 35 .…”
Section: Resultsmentioning
confidence: 99%
“…and post-fusion 12 DENV2-E protein. These residues are overwhelmingly conserved in ZIKV and all DENV serotypes ( Figure 2 ), and are known epitopes 23 , 35 , 39 43 . While perturbation was found to be a good predictor of an epitope, not all epitopes are perturbed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation